Variants of unknown significance on chromosomal microarray analysis: parental perspectives - Jez, Stephanie (J Community Genet, 2015)
Chromosomal microarray is the recommended first-tier genetic test when a child presents with idiopathic developmental delay (DD), intellectual disability (ID), and/or autism spectrum disorder (ASD). Microarray may discover variants of unknown clinical significance (VUS) and been suggested to cause parental stress and anxiety. A retrospective, mixed methods study investigated parental perceptions of chromosomal microarray results that contain VUS. Surveys were sent to parents of children with DD/ID/ASD following a VUS result to seek information regarding parental understanding of the result, perceived value, and perceptions of child vulnerability and parental stress. Parents reported that chromosomal microarray was important for understanding their child’s diagnosis and they were satisfied with the information. A majority of parents reported high confidence in their ability to explain a VUS result to others. Of the parents who reported they received support, many reported that the support was from a genetic counselor. Based on these results, VUS results are important to parents of children with DD/ID/ASD and genetic counseling regarding VUS results contributes positively to both parental understanding and support.